Humanistic Theological Approach In A Political Conspiracy Nai Meko Comunity - Godefridus Meko SVD; Gregorius Neonbasu SVD; Daud Saleh Luji (CV. AFDIFAL MAJU BERKAH, 2023)
The Nai Meko people are the Atoin Meto people who have experienced a winding and complicated history. To study the nuances of faith possessed by the Nai Meko people, the author uses an anthropological approach and aspects of the lives of the people they live. So the purpose of this writing is a contextual effort to read the quality of faith of the Nai Meko people within the framework of the political conspiracy that was experienced during the Portuguese and Dutch colonial periods. The method used in this study is a qualitative method with interview techniques and documentation studies. The interesting thing that exists in the lives of people and the people of Nai Meko every day is, even though they are a society that has been under pressure because of conspiracy politics, they believe in the Most High according to their original religious concept, and they are very deeply rooted in the Catholic faith, so they don't drifting in fatalistic attitudes and lifestyles. In order to maintain harmony in society, the people of Nai Meko develop a dialogical dialogue between the Christian faith and the notion of the Divine by the indigenous religions. It turns out that a theological approach as well as a humanistic pastoral approach is very much needed, so that humans and local communities can be directed to the right and civilized path. Another thing that needs attention is civilized social communication to harmonize two interests, between the Catholic faith and the original religious faith.